THE COMPUTATION OF OCEANIC AND METEOROLOGICAL FIELDS OF MOTION WITH FRICTION PROPORTIONAL TO THE VELOCITY - Wyrtki, Klaus (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1956)
The friction in the hydrodynamical differential equations is taken proportional to the velocity. With it simple relations result, permitting the calculation of the mass transport, without the need to solve differential equations, if the wind and pressure distributions are known. The solution can cross the equator freely. Simultaneously the equations give the vertical components of motion at the lower boundary of the layer under consideration. Numerical values of the friction coefficient are given, and oceanographical and meteorological models are discussed, as for instance the monsoon winds over Southeast Asia, the monsoon currents in the Java and China Seas and the equatorial currents of the Pacific Ocean.